Pearkes, John A.: my recollections (February 23, and August 19, 1971) - Pearkes, John A., b. 1931; Roy, Reginald H. (1971)
An interview/narrative of John A. Pearkes's recollections of Major-General Pearkes. Mr. Pearkes is Major-General Pearkes's son. Interview took place on February 23 and August 19, 1971.; ABSTRACT: John A. Pearkes (son), 23 February 1971. 24pp. (Reel #50, Side 2.) Childhood, his father as a family man. The Pearkes family travels from the perspective of a boy. Life in England during the war. Maj-Gen Pearkes' reaction to a number of events.